Skills for employability Vol.1 - Umesh Pilaniya (Jaipur Satyam Publishers and Distributors, 2021)
essential skills for employability; effective communication skills; how to develop teamwork skills; fundamentals of sampling skills; effectual writing skills; employability planning management skills; tips for time management; problem solving the mark of an independent employee; qualities of superior leaders.
Keywords: Technology